Displacement of Fibrin-bound Thrombin by r-Hirudin Precludes the Use of 131l-r-Hirudin for Detecting Pulmonary Emboli in the Rabbit - Rubens, Fraser D; Ross-Ouellet, Bonnie; Dennie, Carole; Coates, Geoffrey; Kinlough-Rathbone, Raelene L; Hatton, Mark W C (Thrombosis and Haemostasis, 1994)
Pulmonary emboli are detectable by filling defects in the pulmonary vasculature upon pulmonary angiography. Emboli derived from venous thrombi are rich in fibrin to which thrombin remains bound. Hirudin, a specific thrombin inhibitor, binds to thrombin to yield a 1:1 stoichiometric complex. We examined whether 131I-recombinant hirudin (r-hirudin) could be used to detect pulmonary emboli in rabbits. Clots were formed by re-calcifying rabbit plasma in vitro, and then injected (0.034 ml) into a femoral vein to lodge in the lungs. 131I-r-hirudin (29 ± 4 μCi/kg) was injected intravenously but emboli could not be detected by gamma camera in real time. Post-mortem analysis of lung tissue showed that 131I-r-hirudin did not associate with emboli prepared with 125I-fibrin. Because of these findings, we used different techniques to look at the binding of hirudin to plasma clots. Clots formed in vitro were incubated with 131I-r-hirudin in the presence of equimolar amounts of 125I-albumin; specific binding of 131I-r-hirudin was not observed. Experiments with immobilized fibrin(ogen) showed that 125I-r-hirudin did not bind to and remain with fibrin-bound 131I-thrombin but did lead to the inactivation and displacement of up to 70% of bound thrombin as r-hirudin-thrombin complex; residual thrombin bound to fibrin remained active. Thus, released r-hirudin-thrombin complex is probably cleared rapidly from the region of the embolus in vivo; radioiodinated r-hirudin may not, therefore, be useful as a marker for detecting emboli.